Embosphere microsphere embolization of the middle meningeal artery for the treatment of chronic subdural hematoma: a single-center experience - Xu, Ligang; Zhang, Dewei; Jiang, Yeqing; Zhang, Lei; Xu, Jinyan; Zhu, Weiyi; Chen, Wei; Guo, Jun; Gu, Xin; Wan, Jun (Frontiers in Neurology, 2025)
BackgroundTo explore the efficacy, safety, and surgical experience of Embosphere microsphere embolization of the middle meningeal artery (MMAE) in the treatment of chronic subdural hematoma.MethodsA total of 25 patients with chronic subdural hematoma (4 cases with initial treatment, 5 cases with prophylaxis after burr hole drainage, and 16 cases with recurrence after surgical drainage) were selected from the Interventional Therapy Department of Shanghai Jing'an District Central Hospital from October 2022 to December 2024. The patient was treated with bilateral middle meningeal artery embolization under local anesthesia. The recurrence rate of postoperative hematoma and the proportion of patients with maximum hematoma thickness reduction > 50% at 3 months after intervention were used as the main indicators to evaluate efficacy. The complications and operation-related adverse events were observed, and the experience of interventional therapy was retrospectively summarized.ResultsAll 25 patients completed the interventional procedure. Among them, 1 patient underwent unilateral embolization due to the absence of the middle meningeal artery on the affected side, while 24 patients received bilateral embolization. A total of 45 middle meningeal arteries were embolized. After treatment, hematoma absorption and symptoms were improved in all patients, and no recurrence of hematoma was found. The treatment success rate was 100%. The 25 patients were followed up 3 months after the interventional procedure, and the proportion of patients with maximum thickness reduction of hematoma >50% reached 96%. There were no deaths and 2 asymptomatic complications, including 1 hemorrhage complication and 1 ischemia complication. Complications were not related to embolization materials.ConclusionEmbolization of the middle meningeal artery using Embosphere microspheres is safe and effective in the treatment of chronic subdural hematoma. For patients with recurrence or high risk of recurrence, bilateral middle meningeal artery embolization should be considered.